2019
DOI: 10.1101/733477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic and Biological Profiling of Extracellular Vesicles from Alzheimer’s Disease Human Brain Tissues

Abstract: AbstractIntroductionExtracellular vesicles (EVs) from human Alzheimer’s disease (AD) biospecimens contain amyloid-β peptide (Aβ) and tau. While AD EVs are known to affect brain disease pathobiology, their biochemical and molecular characterizations remain ill defined.MethodsEVs were isolated from the cortical grey matter of 20 AD and 18 control brains. Tau and Aβ levels were measur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Among these proteins, GPM6A, a membrane glycoprotein involved in neural differentiation 56 showed high expression in the cerebral cortex, basal ganglia and cerebellum. This molecule has been recently reported as differentially expressed in EV derived from AD brain tissues 57 . In our data, GPM6A was not included in our candidate list, but showed an increasing trend in AD P100 EVs (table S4).…”
Section: Discussionmentioning
confidence: 97%
“…Among these proteins, GPM6A, a membrane glycoprotein involved in neural differentiation 56 showed high expression in the cerebral cortex, basal ganglia and cerebellum. This molecule has been recently reported as differentially expressed in EV derived from AD brain tissues 57 . In our data, GPM6A was not included in our candidate list, but showed an increasing trend in AD P100 EVs (table S4).…”
Section: Discussionmentioning
confidence: 97%
“…We compare the EV proteomics data to human AD brain-derived EV proteomics data (20), the 380 proteins were common between CAST.APP/PS1 brain-derived EVs and human AD brainderived EVs (Supplementary Figure S3). The APOE, CAMKV, ANXA5 and VGF showed a similar correlation with these EVs, suggesting that Ab deposition may be the major pathology for the upregulation of these molecules in EVs.…”
Section: Discussionmentioning
confidence: 99%
“…These EVs contain proteins, mRNA, non-coding RNAs (such as microRNA) and lipids, can transfer these molecules from cells to cells, and can be transported to biofluids, such as and cerebrospinal fluid and blood. In the central nervous system (CNS), brain-derived EVs contain Protein profiling of CAST.APP/PS1 mouse brain-derived EVs 6 multiple AD-associated proteins such as Ab, a-synuclein, APP, cyclin-dependent kinase 5, PSEN1, and tau, and play important roles in Ab deposition and tauopathy (15)(16)(17)(18)(19)(20). Moreover, it has been reported that inhibition of EV synthesis reduced Ab plaque deposition in the mouse model of AD, and stimulation of EV secretion increased intracellular transfer of prion protein in AD mouse models (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Another comprehensive study using label free quantitative proteomics coupled with a machine learning method reported a panel of four exosome proteins that could identify AD patients with 88% accuracy [ 92 ]. These biomarkers were annexin-A5 (ANXA5), NGF-induced growth factor (VGF), neuronal membrane glycoprotein M6-a (GPM6A), and alpha-centractin (ACTZ).…”
Section: Proteomics Approaches In Exosomal Protein Biomarker Discomentioning
confidence: 99%